STATUS OF WOMEN IN THE HOUSEHOLD (MUBADALAH READING AGAINST PATRIARCHAL HADITHS) - Gazali, Gazali; Saputri, Rahma Eka; Efendi, Efendi (Proceeding International Seminar of Islamic Studies, 2023)
The household consisting of husband and wife is the most ancient realm of patriarchal practice. The position of women in the household, which is always interpreted as a servant and generally places women in a disadvantageous position in the family. Especially if patriarchal strength in the family leads to violence against women. If one pulls back the persistent behavior of violence against women in the household, it can occur as an effect of the strong theological narratives about hadiths with patriarchal nuances, which are often interpreted by placing women as passive beings or objects in the family. So this paper aims to explore the actual position of women in the household according to Islam, by reviewing patriarchal hadiths and then reading them from the perspective of mubadalah. This research uses the library research method, concerning several hadiths that are considered patriarchal, then analyzes them using the perspective of mubadalah, to find patterns of mutual relations that should appear in the household. If in the classical interpretation, patriarchal hadiths are interpreted only based on the textual hadith, so they tend to put male pronouns as subjects and women as objects, but through the mubadalah approach, the authors found that men and women in the household could be in the subject position. as well as objects. So that it is not only women who are always seen as objects who must obey serving, but men can also obey by treating their wives with respect and kindness.